Dr. Rafael Meirelles — Deep Plane Facelift — Goiânia - Meirelles, Rafael (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Rafael Meirelles, practicing in Goiânia, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003394; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil; goiânia